2019
DOI: 10.1161/circulationaha.118.038036
|View full text |Cite
|
Sign up to set email alerts
|

Quinidine-Responsive Polymorphic Ventricular Tachycardia in Patients With Coronary Heart Disease

Abstract: Background: Polymorphic ventricular tachycardia (VT) without QT prolongation is well described in patients without structural heart disease (mainly idiopathic ventricular fibrillation and Brugada syndrome) and in patients with acute ST-elevation myocardial infarction. Methods: Retrospective study of patients with polymorphic VT related to coronary artery disease, but without evidence of acute myocardial ischemia. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…It remains unclear, however, whether ischemia–reperfusion injury would be enough to justify this clinical presentation, particularly outside the context of an acute coronary syndrome, or if a pre‐existing channelopathy could have been exacerbated after PCI. Interestingly, a recent case series suggested that CAD‐related but non‐ischemia‐driven drug‐refractory VAs may have a similar background to BrS (and other arrhythmogenic syndromes with a structurally normal heart) and display a remarkable response to quinidine, although in this study there is no mention of a BrP preceding the VAs 5 …”
mentioning
confidence: 63%
“…It remains unclear, however, whether ischemia–reperfusion injury would be enough to justify this clinical presentation, particularly outside the context of an acute coronary syndrome, or if a pre‐existing channelopathy could have been exacerbated after PCI. Interestingly, a recent case series suggested that CAD‐related but non‐ischemia‐driven drug‐refractory VAs may have a similar background to BrS (and other arrhythmogenic syndromes with a structurally normal heart) and display a remarkable response to quinidine, although in this study there is no mention of a BrP preceding the VAs 5 …”
mentioning
confidence: 63%
“…Viskin et al reported quinidine-responsive polymorphic VT in patients with coronary heart disease [10]. In their study, the polymorphic VT in patients with coronary heart disease shared important characteristics with idiopathic VF and Brugada syndrome; the characteristics are distinctive arrhythmia mode of onset by short-coupled extrasystoles and susceptibility to develop arrhythmic storms that are refractory to conventional antiarrhythmic drugs, including amiodarone.…”
Section: Discussionmentioning
confidence: 99%
“…7 Once the electrotonic (suppressive) effects of the surrounding myocardium ceased, early-phase-2 afterdepolarizations (ubiquitous in Purkinje fibers) 8 could have propagated with unidirectional block and reentry within the Purkinje-myocardial junctions, causing very fast arrhythmias. 5,6 J o u r n a l P r e -p r o o f…”
Section: Discussionmentioning
confidence: 99%
“…Fearing the possibility of an arrhythmic storm of polymorphic VT, 4 we started quinidine therapy. 5,6 Intravenous quinidine gluconate (Quinidine Gluconate Injection, Lilly) at a rate of 15 mg/min led to immediate (within minutes) suppression of all ventricular ectopic activity; the infusion rate was then reduced by 50% every 15 minutes until a final dose 2 mg/min was achieved and maintained for a total dose of 800 mg intravenous quinidine gluconate over 4 hours. This was followed by oral hydroquinidine (Serecor, Sanofi) at a dose of 300 mg every 6 hours.…”
Section: Case Reportmentioning
confidence: 99%